Who gets to speak? How institutions and political careers shape gender bias in South Africa’s parliamentary debates - Sanches, E. R.; Espírito-Santo, A. (Politics and Gender, 2026)
How does gender shape patterns of parliamentary speechmaking? We theorize and test three types of effects. The direct effect posits that female MPs speak less than their male peers. The access effect claims that the feminization of parliaments and parties is associated with higher gender bias in speech levels. The career effect foresees a greater gender bias in speech levels among MPs holding positions of power. Drawing on parliamentary speeches in South Africa (1999–2024), where high rates of female representation coexist with sexist norms and practices, we find evidence for all three effects. Female MPs make fewer speeches, and the growing feminization of institutions and the appointment of female MPs to leadership roles are not sufficient to reverse entrenched gender biases against women. Our findings highlight the need to go beyond the politics of presence and focus on the informal mechanisms that hinder women from performing their roles even when occupying positions of power.